Thinking in fine arts as a problem of modern and foreign philosophy - Akbayeva, Sholpan A.; Alina N. Lobanova, Zhanar S. Kenessarina, Ardak A. Nigmeto , Abduali T. Tolebiev, Inna M. Zayats, (Opción, 2019)
The authors analyzed the phenomenon of freedom of creativity in artistic culture via the historical, cultural and artistic-philosophical approaches. As a result, many new facts, concepts, names entered the scientific circulation. Promising were the studies of socialist realism as a special discursive practice or the space of patron-client relations and informal networks of influence. In conclusion, Russian researchers are less likely to have theoretical ambitions; they are engaged in gathering facts and publicistic assessments of the past while domestic experts are more interested in the political aspects of the history of art.